2003
DOI: 10.1002/rmv.372
|View full text |Cite
|
Sign up to set email alerts
|

Natural and synthetic sialic acid‐containing inhibitors of influenza virus receptor binding

Abstract: Influenza viruses attach to susceptible cells via multivalent interactions of their haemagglutinins with sialyloligosaccharide moieties of cellular glycoconjugates. Soluble macromolecules containing sialic acid from animal sera and mucosal fluids can act as decoy receptors and competitively inhibit virus-mediated haemagglutination and infection. Although a role for these natural inhibitors in the innate anti-influenza immunity is still not clear, studies are in progress on the design of synthetic sialic acid-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
120
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(127 citation statements)
references
References 78 publications
5
120
0
2
Order By: Relevance
“…On the other hand, monomeric HA1 did not agglutinate RBCs even in the presence of anti-His antibodies (Fig. 3C, second row), suggesting that interaction between monomeric HA1(1-320) and the sialyloligosaccharides moieties is rather weak (16). The N-terminal HA fragment (amino acids 1 to 104) formed oligomers (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, monomeric HA1 did not agglutinate RBCs even in the presence of anti-His antibodies (Fig. 3C, second row), suggesting that interaction between monomeric HA1(1-320) and the sialyloligosaccharides moieties is rather weak (16). The N-terminal HA fragment (amino acids 1 to 104) formed oligomers (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The His 6 -tagged fusion proteins were purified using Ni-NTA chromatography to Ͼ95% purity ( Agglutination of red cells is a surrogate for the binding of influenza virus to its sialic acid receptors. The interaction between individual HA RBD and the sialyloligosaccharides moieties is rather weak (K d Ͼ 10 Ϫ4 M) (16), and increased avidity is accomplished by binding of multimeric HA spikes to multiple cell receptors. To determine whether the recombinant HA1 proteins contain functionally active forms, they were evaluated in a human RBC hemagglutination assay.…”
Section: Resultsmentioning
confidence: 99%
“…None of the currently available drugs is directed at the hemagglutinin, which is one of the major membranal surface glycoproteins of the virus. Several compounds were reported to achieve antiinfluenza activity by targeting the HA (mostly sialic acid analogues), but their effectiveness has not been described in definite terms (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that cyclophilin A which is widely distributed in a variety of chicken tissues and localized in the cytoplasm of CEF cells inhibits virus replication by interfering with the translocation of newly synthesized M1 protein into nucleus in the early stage of infection (Xu et al 2010;Liu et al 2009). FBS contains a variety of inhibitory components, termed b-inhibitors, that bind to N-linked glycans on HA and NA and inhibit receptor-binding, hemagglutinating activities and the infectivity of influenza virus (Matrosovich and Klenk 2003). Despite of similarities of virus replication dynamic, difference in HA titer was observed between both cells.…”
Section: Discussionmentioning
confidence: 99%